Probing the intrinsic phonon transport properties of the SnTe thermoelectric material. (September 2021) - Yang, Bin; Li, Shuangming; Li, Xin; Liu, Zhenpeng; Li, Dou; Zhong, Hong; Feng, Songke
Abstract: Based on the Boltzmann transport theory combined with first-principles calculations, we analyze the lattice anharmonicity of SnTe and the respective contributions of the lattice thermal conductivity ( κ L ) from six different phonon modes. The Grüneisen parameter ( γ ), three-phonon scattering phase space ( SPS ), phonon lifetime ( τ ), and phonon velocity ( v ) were obtained quantitatively. These calculations indicate that large τ with maximum value of 104 ps and high v of 4800 m/s for acoustic branches make the acoustic modes a major contributor to the high κ L of SnTe (～78% for acoustic branches and ～22% for Optical branches). Further, the dependence of κ L on phonon mean free path shows that designing nanostructures with characteristic length of less than 14.5 nm could be an effective way to decrease the κ L . In addition, we employed high-temperature gradient directional solidification technique to grow the SnTe single crystal and the measured κ L vaules of the single crystal match reasonably with the theoretical calculation results. Highlights: Lattice anharmonicity of SnTe was investigated based on first-principles calculations. The respective contributions of κL from six different phonon modes were computed quantitatively. The theoretical calculation results of the κL agree well with the experimental values of the single-crystal SnTe. Designing nanostructures with characteristic length of less than 14.5 nm could be an effective way to decrease the κL .